2023
DOI: 10.4081/qrmh.2022.10241
|View full text |Cite
|
Sign up to set email alerts
|

Near-death experiences and the change of worldview in survivors of sudden cardiac arrest: A phenomenological and hermeneutical study

Abstract: Near-death experiences (NDEs) can occur during episodes of unconsciousness from life-threatening conditions, such as sudden cardiac arrests (SCAs). This study is based on interviews with patients who had an NDE. The interviews were analyzed with phenomenological hermeneutical method for their lived experiences and the meaning for the view of life and death. Four participants were interviewed 10 weeks after their NDE. Four themes emerged: being on the other side, in another dimension; not dreaming, this is a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Characteristics of the included studies are presented in Table 1 . Three studies were conducted in Slovenia [ 7 9 ], two in the USA [ 10 , 11 ], one in the UK [ 12 ], one in the Netherlands [ 13 ], one in Austria [ 14 ], one in Sweden [ 15 ], and two international studies [ 16 , 17 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Characteristics of the included studies are presented in Table 1 . Three studies were conducted in Slovenia [ 7 9 ], two in the USA [ 10 , 11 ], one in the UK [ 12 ], one in the Netherlands [ 13 ], one in Austria [ 14 ], one in Sweden [ 15 ], and two international studies [ 16 , 17 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…For example, in one study, which found a incidence of 18%, near-death experience was defined based upon the reported memory of impression of having experienced an altered state of consciousness, rather than a validated scale [ 13 ]. The inclusion of in-hospital cardiac arrest patients (reported near-death experience incidences of 10% [ 10 ], 6.3% [ 12 ], 6.4% [ 16 ], 23% [ 11 ], 39.3% [ 17 ], 15.9% [ 14 ], 16.7% [ 15 ], and 18%[ 13 ]) as opposed to only out-of-hospital cardiac arrest (reported near-death experience incidences 21.2% [ 9 ], 21.2% [ 8 ], 18.9%[ 7 ]), may contribute to variation. All included studies involved interviews.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation